A review of inorganic photoelectrode developments and reactor scale-up challenges for solar hydrogen production - Moss,B; Babacan,O; Kafizas,A; Hankin,A (Advanced Energy Materials, 2021)
Green hydrogen, produced using solar energy, is a promising means of reducing greenhouse gas emissions. Photoelectrochemical (PEC) water splitting devices can produce hydrogen using sunlight and integrate the distinct functions of photovoltaics and electrolyzers in a single device. There is flexibility in the degree of integration between these electrical and chemical energy generating components, and so a plethora of archetypal PEC device designs has emerged. Although some materials have effectively been ruled out for use in commercial PEC devices, many principles of material design and synthesis have been learned. Here, the fundamental requirements of PEC materials, the top performances of the most widely studied inorganic photoelectrode materials, and reactor structures reported for unassisted solar water splitting are revisited. The main phenomena limiting the performance of upscaled PEC devices are discussed, showing that engineering must be considered in parallel with material development for the future piloting of PEC water splitting systems. To establish the future commercial viability of this technology, more accurate technoeconomic analyses should be carried out using data from larger scale demonstrations, and hence more durable and efficient PEC systems need to be developed that meet the challenges imposed from both material and engineering perspectives.